Synthesis and Metal Ion Probe Properties of Four 1,8-Naphthalimides - Liu, Qian; Fang, Yilin; Yi, Xianghui; Chen, Rui; Zhang, Ye (Asian Journal of Chemistry, 2013)
Four 1,8-naphthalimide derivatives (3a-3d) were designed and synthesized from 1,8-naphthalic anhydride and their structures were characterized by 1H NMR and MS. Their recognition ability to metal ions was then investigated. The results showed the quenching constants (KCV) and binding constants (Ka) values were found in the range of 102-104 M-1, indicating important metal ions recognition abilities of compounds 3a-3d. All the compounds showed recognition of ferric ion, while compounds 3a-3d showed the best recognition ability of silver, cadmium, ferric and ferrous ions, respectively.